"går litt for meg selv og rekrutterer..." Kateketens rekrutterende yrkespraksis (Tidsskrift for Praktisk Teologi, 2019)
This paper explores how catechists reflect on their own professional practice as a recruiting area for young people into work in the church. The data material is established through qualitative interviews. An important part of the catechist’s profession involves various communities of practices with adolescents. Drawing on the concepts of legitimate peripheral participation by Wenger (1998) this study seeks to understand how the catechists reflect on their professional practices between differentcommunities of practices and how the catechists opens or constraints the young people to work in the Church of Norway. The study argues for a better understanding of the complex dynamic concerning participation in order to open for participation of the young people into the catechists’ and other ministry professional practices.